DECONSTRUCTING PRESENCE IN STRANGER THINGS 4: TRACE, SUPPLEMENT, HAUNTOLOGY, AND ITERABILITY - Dahlan, A. Fahmi (Universitas Padjadjaran, 2026)
This article examines Stranger Things 4 (ST4) as a case of how contemporary serial television manufactures presence from inherited signs. Using a Derridean framework—trace, supplement, hauntology, and iterability—it analyses four binaries (past/present, child/adult, real/monster, original/homage) and shows how each is destabilized through scenes, sounds, and props. Methodologically, the study combines deconstructive close reading with intertextual mapping, sound–image alignment, and motif tracking across episodes and paratexts. Sources include transcripts, promotional materials, and repeated viewings. Analytic steps comprise open coding of binary markers, axial clustering around Derridean mechanisms, and synthetic memoing checked against scholarship. Findings indicate that the ‘1980s’ functions as a trace that pre-organizes the present; that youth action supplements, and thereby exposes, adult authority; that reality appears haunted by what communities refuse to narrate; and that originality emerges from iterated citation rather than pure origin. Across these domains, analog devices and music do not merely decorate narrative time; they compose it, converting memory into method and fear into coordination. The thesis contributes to popular culture studies by showing how deconstruction operates as an analytic of production not a negation of meaning. It also offers a matrix for reading other nostalgia-led series and for understanding audience practices that transform homage into infrastructure. The study argues that ST4 advances an ethic of responsible repetition: reading traces, accepting supplements, listening to specters, and reshaping inheritances into forms that sustain attention, care, and sense.